Religious values and business angel investment decision-making: the influence of the Jewish ethos Tikkun Olam - Berdugo, Ethel Victoria Sarah (2022)
This study investigates the role of religious values in the investment decision-making process of Jewish business angels. We show that respondents’ worldview is influenced by Jewish spiritual principles, specifically Tikkun Olam, which affects their investing behavior by providing them with motivational and attitudinal orientation. Life-story interviews were conducted with 15 business angels based in France, Brazil, and Israel. Using thematic analysis, we identified Tikkun Olam-related dimensions on which respondents’ decision-making tended to rely. Themes such as collective cohesion, values alignment, world improvement, and mystical beliefs took the leading role over traditional wealth-maximization factors expected in investment decision-making. This work shows that non-rational, social identity-related factors support business angels' decision- making and help them cope with early-stage investment's high risk and uncertainty.